We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
448
2
avatar+211 

\(T(s) = \frac{G(s)}{1+N(s)G(s)}\)

 

if \(G(s) = \frac{10s}{(s+3)(s-2)}\)and \(N(s)=s+2\)

simplify the expression for T(s)

 

I'm in 2 minds about this...

 

I just want to cancel the G functions out on the top and bottom and then be left with, \(\frac{1}{1+(s+2)}\)

 

however my other brain is saying I need to do the arithmetic and see what I get.

 Mar 29, 2017
 #1
avatar+100803 
0

Mmm

 

\(T(s) = \frac{G(s)}{1+N(s)G(s)}\)

 

Immediately I a restraint  \(N(s)G(s)\neq -1\)

so

\((s+2)*\frac{10s}{(s+3)(s-2)}-1\ne0\\ 10s(s+2)-(s+3)(s-2)\ne0\\ 10s^2+20s-(s^2+s-6)\ne0\\ 10s^2+20s-s^2-s+6\ne0\\ 9s^2+19s+6\ne0\\ s\ne \frac{-19\pm\sqrt{145}}{18}\)

 

 

 

\(G(s) = \frac{10s}{(s+3)(s-2)}\\so\\ s\ne-3,\quad s\ne2 \\ N(s)=s+2 \)

 

 

\(T(s)=\frac{\frac{10s}{(s+3)(s-2)}}{ 1+(s+2)\frac{10s}{(s+3)(s-2)}}\\ T(s)=\frac{\frac{10s}{(s+3)(s-2)}}{ 1+(s+2)\frac{10s}{(s+3)(s-2)}}\times \frac{(s+3)(s-2)}{(s+3)(s-2)}\\ T(s)=\frac{10s}{(s+3)(s-2)+(s+2)10s}\\ T(s)=\frac{10s}{s^2+s-6+10s^2+20s}\\ T(s)=\frac{10s}{11s^2+21s-6}\quad where \;\;s\neq 2,-3,\frac{-21\pm\sqrt{705}}{22},\;or\;\frac{-19\pm \sqrt{145}}{18}\)

.
 Mar 29, 2017
 #2
avatar+211 
0

thank you melody, I appreciate it

 Mar 29, 2017

30 Online Users

avatar